(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
the issue of environmental pollution requires actions as well as words, because pollution may lead to a natural disaster with dire consequences in the future. Therefore, people must be more aware of this matter and take serious steps to reduce environmental pollution, air, water and soil. In order to preserve the environment in which he lives and not be the cause of his own extinction in the end. The forms and forms of environmental pollution are many and varied according to their degree (strength) and their source or cause. In terms of degree, pollution is divided into three degrees: acceptable pollution, and dangerous pollution that you suffer from. From it most industrialized countries, and destructive pollution that leads to the collapse of the ecosystem, and in terms of source, pollution is divided into natural pollution and pollution resulting from human activity. This research aims to study the forms of pollution resulting from human activity and how to reduce its danger as much as possible. The research studies the following forms of Pollution is water, air and soil pollution, solid and hazardous waste pollution, noise and radiation pollution, biological pollution, indoor pollution and finally moral pollution represented by cultural, media, moral and intellectual pollution. The phenomenon of pollution has become a global problem, and therefore many international organizations and institutions have emerged that have taken it upon themselves to address this serious problem.